Impact of seedlings age on vegetable Marrow production (SAARC Journal of Agriculture, 2015)
A study was conducted at the research field of Horticultural Research Institute, National Research Center (NARC), Islamabad, Pakistan during two consecutive years of 2011 and 2012 to compare the performance of seedlings raised in polythene bags with traditional direct seeding in respect of early harvesting and profitability. Seedlings of three different ages (40, 50 and 60 days old) of vegetable marrow were compared with traditional direct seeded crop. Transplanted seedlings of vegetable marrow produced fruits 36-38 days earlier and availability period of 34-38 days longer than direct seeded crop. Similarly, higher fruit plant-1, fruit weight plant-1 and fruit yield ha-1 were obtained from seedling treatments. Averaged over years, 50-69% increase in yield and 64-100% increase in profit were recorded in seedling treatments than direct seeded crop. Among seedling ages, 60 days old seedlings were the best performer. The overall results of two years study revealed that seedling transplantation was superior to traditional direct seeded practice of growing vegetable marrow and among those 60 days old seedlings was the best in respect of yield components, fruit yield and profit.SAARC J. Agri., 13(1): 215-222 (2015)